so hmm -6, -4, -2, 0? what the heck is going on?
well, from -6 to -4, is really a +2 "difference", and from -4 to -2 is the same amount. So to get the next term's value, you simply "add 2", therefore, 2 is the "common difference" in this arithmetic sequence.
let's also notice that -6 is our first fellow.
[tex]\bf n^{th}\textit{ term of an arithmetic sequence}\\\\
a_n=a_1+(n-1)d\qquad
\begin{cases}
n=n^{th}\ term\\
a_1=\textit{first term's value}\\
d=\textit{common difference}\\
----------\\
d=2\\
a_1=-6\\
n=13
\end{cases}
\\\\\\
a_n=-6+(13-1)2\implies a_{13}=-6+(13-1)2
\\\\\\
a_{13}=-6+(12)2\implies a_{13}=-6+24\implies a_{13}=18[/tex]